Troska o zdrowie prokreacyjne w naprotechnologii ─ formą budowania nowej kultury życia ludzkiego - Bassa, Bożena (Teologia i Moralność, 2017)
NaProTECHNOLOGY is a new field of medicine specializing in the promotion of human procreation. Its foundation is a teaching system called the Creighton Model Fertility Care System. It is based on the ability to observe and record biological biomarkers, enabling spouses to recognize and understand the naturally occurring cycle of fertility and infertility. The spouses can use their acquired knowledge both for achiving pregnancy and avoiding pregnancy. The system also enables them to broaden their knowledge to better understand sexuality and deepen their mutual love. It also plays an important role in diagnosing and treating reproductive health according to the natural cycle of women. NaProTECHNOLOGY is involved in building a "new culture of life" through integral concern for human fertility by restoring natural procreation and respecting the principles of responsible parenthood.